Métodos de multiplicación del babaco (Carica pentagona L.) por injertos - Soria V, M. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
"Babaco" (Carica pentagona L.) is a parthenocarpic species and it is multiplied mainly by cuttings. Successful trials of two types of graftings on young seedlings of "chamburo" (Carica puboscens L) are reported. The more efficient method was by terminal graftings although lateral graftings were also efficient.